Amplifying the antidiabetic actions of glucagon‐like peptide‐1: Potential benefits of new adjunct therapies. Issue 12 (7th October 2021) - Tanday, Neil; Flatt, Peter R.; Irwin, Nigel
Abstract: Clinically approved for the treatment of diabetes and obesity, glucagon‐like peptide‐1 (GLP‐1) receptor agonists display prominent glucose‐ and weight‐lowering effects as well as positive cardioprotective and neuroprotective actions. Despite these benefits, bariatric surgery remains superior in producing robust and sustained weight loss alongside improvements in metabolic control with possible diabetes remission. The current review considers the potential for adjunct therapies to augment the therapeutic actions of GLP‐1 receptor agonists. In this regard, several gut‐derived hormones also, modulated by bariatric surgery, display additive properties when combined with GLP‐1 receptor agonists in both preclinical and clinical studies. In addition, glucocorticoids and oestrogen have shown promise in augmenting the biological actions of GLP‐1 in animal models. Additionally, GLP‐1 efficacy can also be enhanced by use of compounds that prolong GLP‐1 receptor coupling to potentiate downstream receptor signalling. Taken together, therapies that activate GLP‐1 receptor signalling, in combination with various other cell signalling pathways, show potential for treating type 2 diabetes and obesity with superiority over GLP‐1 receptor agonist therapy alone. What's new?: GLP‐1 receptor agonists exert multi‐organ metabolic benefits to treat type 2 diabetes and obesity. Despite this, intolerable GI side effects restrict this class of therapy from use in some patients. This paper reviews the preclinical and clinical data regarding adjunct therapies for GLP‐1 The improved efficacy and safety profile of adjunct therapies, in particular dual‐acting GLP‐1, GIP and triple‐acting GLP‐1, GIP, glucagon receptor agonists, promises to further improve type 2 diabetes treatment.